Anti-Inflammatory Effect of L-carvone on Lipopolysaccharide-Induced Acute Lung Injury - Mahde, Samah; Sarmad H. Kathem (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Acute lung injury (ALI) is among the most serious conditions characterized by an exacerbation of inflammatory response that can result from a persistent lung infection. Carvone is chiral monoterpenoid ketone present in the essential oils of dill, caraway, and spearmint. It shows antioxidant, anti-inflammatory, and antimicrobial effects among others. In this study, the lung anti-inflammatory and protective effects and potential mechanism of action of carvone were investigated in ALI induced by Lipopolysaccharide (LPS).